2000
DOI: 10.1097/00001703-200010000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis-associated infertility

Abstract: This review summarizes the recent literature examining the relationship between endometriosis and infertility. It is clear that the advanced stage of the disease and the mechanical disruption of the pelvic anatomy may cause infertility. The link between early stage endometriosis and infertility remains a source of controversy. Management plans must be individualized contingent upon the stage of disease, the age of the patient and the duration of infertility. The preponderance of data suggests that ablative the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 31 publications
2
28
0
5
Order By: Relevance
“…Several investigations have generated support for the association between endometriosis and infertility, but a specific cause and effect relationship yet is not established. Traditionally, endometriosis-associated infertility has been attributed to primarily advanced stages of pelvic disease, which cause lesions including tubal and ovarian adhesions that may, through mechanical means, impair normal reproductive processes [3]. Panidis et al [12] reviewed the putative mechanisms of early-stage endometriosis in the etiology of subfertility.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have generated support for the association between endometriosis and infertility, but a specific cause and effect relationship yet is not established. Traditionally, endometriosis-associated infertility has been attributed to primarily advanced stages of pelvic disease, which cause lesions including tubal and ovarian adhesions that may, through mechanical means, impair normal reproductive processes [3]. Panidis et al [12] reviewed the putative mechanisms of early-stage endometriosis in the etiology of subfertility.…”
Section: Introductionmentioning
confidence: 99%
“…Surgically induced endometriosis in rats results in decreased fecundity (3), and intraperitoneal injections of peritoneal fluid (PF) from women with endometriosis into mice lowers the implantation rate (4). Moderate or severe endometriosis causes infertility due to mechanical disruption of ovulation or efficient gamete transport (5). Even in its mildest forms, endometriosis may contribute to infertility (6).…”
mentioning
confidence: 99%
“…Controlled Ovarian Hyperstimulation (COH) with or without Intrauterine Insemination (IUI) RCTs evaluating the efficacy of ovulation induction with or without IUI have demonstrated that ovulation induction increases conception rates in endometriosisassociated infertility with no disrupted pelvic anatomy or male factor infertility [1,50,[67][68][69][70] ( table 4 ). Guzick et al [71] compared fecundity rates after randomizing their patients into intracervical insemination (ICI), intrauterine insemination (IUI), gonadotropin induction/ICI, and gonadotropin induction/IUI.…”
Section: Assisted Reproductive Technologies In Endometriosis-associatmentioning
confidence: 99%
“…retrieval and inferior laboratory methodologies used in early studies may explain this inconsistency [67] . Enhanced conception rates with increasing disease stage have also been noted [77] .…”
Section: Assisted Reproductive Technologies In Endometriosis-associatmentioning
confidence: 99%